Pengembangan Platform Gamifikasi pada Museum Berbasis Kuis Menggunakan Design Thinking - Nur Noftianto, Eko Felix (JATISI, 2025)
Museums play a crucial role in preserving and disseminating knowledge about history, culture, art, and science. However, digital advancements challenge museums to stay relevant and appealing to tech-savvy younger generations. One solution is quiz-based gamification, which combines game elements with educational content to create interactive learning experiences. This study aims to develop a learning strategy through quiz-based gamification in museums, focusing on improving visitor engagement and understanding. The design thinking method was used, consisting of five stages: empathize, define, ideate, prototype, and test. During empathize, observations and interviews showed that traditional methods often fail to engage visitors. The define stage identified a lack of motivation for active learning as the main issue. In ideate, a quiz-based concept was designed using elements like challenges, rewards, points, levels, and competition. The prototype stage involved creating an interactive quiz, while test evaluated it with visitors. Results showed increased engagement and understanding. In conclusion, quiz-based gamification effectively enhances learning outcomes, transforming museums into interactive spaces that combine education and entertainment, making them more appealing and relevant to younger generations in the digital era.